Effect of Dietary Supplementation of Amla (Phyllanthus emblica, Syn. Emblica officinalis) on Growth and Health of Commercial Broiler Chicken (CARIBRO Dhanraja) - Dey, Anshuman; Chatterjee, J. K.; Rao, Y. Vasudeva (International Journal of Bio-resource and Stress Management, 2023)
The present research work was performed at Rathindra Krishi Vigyan Kendra, Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati, Sriniketan, Birbhum, West Bengal, during February–April 2022. The objective of the present study was to explore the effect of dietary supplementation of amla (Emblica officinalis) on the health and growth of broiler chicks (CARIBRO Dhanraja). A total of thirty-six (36) one-day old chicks were randomly distributed into three dietary treatment groups with three replicates for each treatment group and four birds in each replicate to conduct the proposed study. The three experimental dietary treatments were, Control group, fed with standard diet, i.e., without amla (E. officinalis) supplementation (T1), Test groups, fed with 1.5% amla (E. officinalis) supplemented diet (T2) and 2.5% amla (E. officinalis) supplemented diet (T3). From the results, the highest average body weight, highest weekly average body weight gain and better Feed Conversion Ratio were observed in T2 followed by T3. It was found that serum SGPT/ALT, SGOT/AST and ALP levels were found to be highest in the control group (T1), and were significantly reduced in amla-supplemented groups, least levels were observed in the T3 group. There was no significant difference observed in dressing yield among the treatments. However, in some carcass parameters, a significant difference was observed among the groups with different treatments. From the above study, it could be concluded that feed supplemented with amla (E. officinalis) improved the health and growth of the broiler chicken, which is economically profitable to the poultry farmers.